Fixed Collocations with Epitheta Ornantia in the Livonian Rhymed Chronicle in Terms of Historical Pragmalinguistics - E. S. Tikhonova (Дискурс, 2023)
Introduction. The paper  considers  Middle High German  poetic  nominations  of a warrior such as helt ‘hero’, ritter ‘knight’ and degen  ‘warrior’ combined  with epitheta  ornantia.  The aim of this paper is to find out the most characteristic contexts  for these  lexemes.Methodology and sources. The research is based on methodology of historical pragmalinguistics and cognitive linguistics, in particular on the frames’ theory by Ch. Fillmore. As material for the research serves the Livonian Rhymed Chronicle (late XIIIth cent.), written in the East Middle German dialect. The text’s linguistic features  are scarcely studied by historical linguists in Russia. The Chronicle was written under the influence of courtly epics, which fact was discussed by U. Arnold, M. Fischer, H. Kugler, A. Murray and others.Results and discussion. In the Chronicle’s text there  were selected  10 frames  that include the  analyzed  nouns  with epitheta   ornantia.  The  noun  helt  can  also  be  found  in parts including and introducing  direct  speech.  Each of the  three  nouns  was analyzed as  to  in which frames it is attested and which epitheta  are more common in each frame.Conclusion. A  conclusion  was drawn that  the  noun  helt  ‘hero’  appears  in almost  all the frames,  ritter  ‘knight’  appears  mostly  in frames  that  refer  to  static  situations  and  degen ‘warrior’ – in frames that refer to dynamic situations. Moreover, the lexeme  helt ‘hero’ has a wider distribution range in the Chronicle than the other two nouns.